Perbandingan Perlindungan Hukum Berbasis Undang – Undang Nomor 28 Tahun 2014 Tentang Hak Cipta Dan Digital Millennium Copyright Act (DMCA) Terhadap Karya Musik yang Dipublikasikan Ulang di YouTube Tanpa Izin - Alezandro Pitter Siwi; Lesza Leonardo Lombok; Susi Aryani Manangin (INVENTION: Journal of Intellectual Property Law, 2025)
The development of digital technology has facilitated the distribution of works, including songs, through platforms such as YouTube, but also increased the risk of copyright infringement. This study analyzes legal protection for copyright holders of songs republished on YouTube without authorization. The method used is normative juridical with a statutory and case study approach. The results show that although Law Number 28 of 2014 provides copyright protection, challenges remain in its digital implementation. Therefore, this study compares it with the Digital Millennium Copyright Act (DMCA) in the United States, which offers a notice-and-takedown mechanism. The comparison highlights the need to strengthen Indonesia's digital copyright protection through collaboration between the government, platforms, and the public.